18F-FDG PET/CT Brain in a Case of Agrammatic/Nonfluent Variant of Primary Progressive Aphasia (Broca's Aphasia). (May 2020) - Kousik, Vankadari; Mittal, Bhagwant Rai; Kumar, Rajender; Singh, Harmandeep; Goyal, Manoj
Abstract : Abstract: Primary progressive aphasia is a neurodegenerative variant of frontotemporal lobe degeneration presenting with isolated selective impairment of language domain, not secondarily due to stroke. We present a case of middle-aged female patient who underwent 18 F-FDG PET of the brain for evaluating progressively declining speaking ability associated with altered fluency of speech and occasional mutism. 18 F-FDG PET revealed asymmetric hypometabolism involving the left inferior frontal gyrus along with left anterior cingulate gyrus suggestive of Broca's aphasia.